Taşra burjuvazisinin tarihsel kökenleri - (:unkn) unknown (My University, 2010)
Özet: Bu makale, beş ayrı kentte yürüttüğümüz (Muğla, Aydın, Denizli, Gaziantep, Kahramanmaraş) araştırma çerçevesinde eşraf ailelerinden kişilerle gerçekleştirdiğimiz sözlü tarih görüşmeleri ile kentin sanayi, ticaret ve kültür hayatında etkin kişilerle yaptığımız görüşmelere dayanmaktadır. Makalede, esas olarak, görüşmelerde elde ettiğimiz bilgiler ve sözlü anlatılar, burjuva işveren sınıfı, rantiyer ve eğitimli orta sınıflar olarak "sosyal sınıf oluşumlarına giden yollar"ı belirlemek üzere değerlendirilerek, eşraf ailelerinin bu kentlerde ekonomik, sosyal, politik alanda aktörler olarak etkilerinin sürüp sürmediği araştırılmıştır. Araştırma sonuçlarına göre, Türkiye'de eşraf aileleri, taşra burjuvazisinin oluşumunda tarihsel bir öneme sahip olmakla birlikte, özellikle 1980 sonrası ekonomik süreçte ekonomik olarak güçlenen ve küresel ekonomiye eklemlenen yeni sermaye grupları ve yatırımcılar da kentsel aktörler arasına girmiştir. Eşraf ailelerinde iki kuşak arasında eğitimde, meslek seçimi, girişimcilik ve işadamı kimliğinde, politik seçimlerde gerçekleşen değişmeler, taşra kentlerinde bugün farklı stratejilerle kendilerini gösteren "kent seçkinlerinin ve "kentli orta sınıflar"ın oluşumunda eşraf ailelerinin etkisinin ekonomik alanda olmasa bile sosyal alanda sürdüğünü göstermektedir.

This article is based on research which was carried out in five cities in Turkey, namely, Muğla, Aydın, Denizli, Gaziantep, and Kahramanmaraş, oral history interviews with members of locally notable families and interviews with persons influential in the industrial, commercial and cultural lives of these cities. The question of whether the influence of locally notable families still persists is investigated through data collected and the oral narratives of these interviews, and is evaluated basically according to different paths to social class formation such as the bourgeois business class and rentiers or educated middle classes. According to the findings of the research, even though historically notable local families have significantly influenced the formation of a local bourgeoisie in Turkey, new groups of capitalists and entrepreneurs that have grown and integrated with the global economy in the economic process after the 1980s have also become urban actors. In different generations of notable local families, the changes in education, occupational choice, en-trepreneurship and businessman identity, as well as in political choices show that local notable families still have influence on the formation of the local elite and urban middle class in provincial cities in Turkey and they exploit different strategies to mark their difference and maintain their influence in the social sphere, if not in the economic sphere today.
The historical roots of the provincial bourgeoisie in Turkey
Keywords: Tarih